Basic education in rural area the case of parents involvement in Tambunan Sabah / Jerseyla Sakim and Mastecca Theclla James - Sakim, Jerseyla; James, Mastecca Theclla (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2014)
Basic Education is very crucial for an early education. Nonetheless, it has considered as a pertinent issue in Malaysia. This has led to a claim that Malaysia students are left behind especially in mastering languages, Mathematics, and Science. This study took place in one of the rural area in Sabah that is Tambunan, which focuses on the parents' level of involvement in basic education and to identify factors associated to basic education. A set of 200 questionnaires randomly distributed in four villages within Tambunan District. Surprisingly, the degree of the level of parents· involvement in the study area for basic education was positively high. This study also reveals that factors of parents' involvement in basic education have a strong relationship with parents' communication and parent’s roles.